African Trypanosome-Induced Blood–Brain Barrier Dysfunction under Shear Stress May Not Require ERK Activation - Sumpio, Brandon J.; Chitragari, Gautham; Moriguchi, Takeshi; Shalaby, Sherif; Pappas-Brown, Valeria; Khan, Asif M.; Sekaran, Shamala Devi; Sumpio, Bauer E.; Grab, Dennis J. (International Journal of Angiology, 2015)
African trypanosomes are tsetse fly transmitted protozoan parasites responsible for human African trypanosomiasis, a disease characterized by a plethora of neurological symptoms and death. How the parasites under microvascular shear stress (SS) flow conditions in the brain cross the blood–brain barrier (BBB) is not known. In vitro studies using static models comprised of human brain microvascular endothelial cells (BMEC) show that BBB activation and crossing by trypanosomes requires the orchestration of parasite cysteine proteases and host calcium-mediated cell signaling. Here, we examine BMEC barrier function and the activation of extracellular signal-regulated kinase (ERK)1/2 and ERK5, mitogen-activated protein kinase family regulators of microvascular permeability, under static and laminar SS flow and in the context of trypanosome infection. Confluent human BMEC were cultured in electric cell-substrate impedance sensing (ECIS) and parallel-plate glass slide chambers. The human BMEC were exposed to 2 or 14 dyn/cm2 SS in the presence or absence of trypanosomes. Real-time changes in transendothelial electrical resistance (TEER) were monitored and phosphorylation of ERK1/2 and ERK5 analyzed by immunoblot assay. After reaching confluence under static conditions human BMEC TEER was found to rapidly increase when exposed to 2 dyn/cm2 SS, a condition that mimics SS in brain postcapillary venules. Addition of African trypanosomes caused a rapid drop in human BMEC TEER. Increasing SS to 14 dyn/cm2, a condition mimicking SS in brain capillaries, led to a transient increase in TEER in both control and infected human BMEC. However, no differences in ERK1/2 and ERK5 activation were found under any condition tested. African trypanosomiasis alters BBB permeability under low shear conditions through an ERK1/2 and ERK5 independent pathway.
Keywords: African trypanosomes; blood–brain barrier; brain microvascular endothelial cells; trypanosoma brucei rhodesiense; shear stress; MAPK